Tripoli Harbor in Ottoman Era (1516-1916) - Youssef, Ilham; Youssef , Mohammad (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
With the beginning of the Ottoman era, Tripoli harbor enjoyed great importance. It was considered the main harbor of Aleppo till 1612. Likewise Tripoli was a resident city for foreign minorities, and other States representatives (Consuls) However, it lost its status with the commencement of the 17th century. Tripoli faced several circumstances that led to decline of its harbor. In the first half of the 17th century, Tripoli suffered from Youssef Basha Seifa’s despotism, and his embezzlement of foreign merchant’s money. Likewise the city suffered from his severe enmity with Prince Fakhr Edin El Mani II. This rift led to the progress of Iskandaron Harbor The Industrial Revolution in Europe led to the flow of commodities from Europe to Levant. This nictitated the building of Beirut Harbor, which soon diminished Tripoli Harbor. With the end of the 19th century, the harbor lost its importance after the installation of the railway Riaque- Aleppo, that used to transport commodities to Riaque, a meeting point between Homs, Hama, Beirut and Al-Sham, then the commodities would be carried to the ships waiting at Beirut. This led to losing internal trade of Tripoli with both Homs and Hama.